Inclusión de tres niveles (2, 4 y 6%) de harina de plátano verde (Musa x paradisiaca) como fuente de carbohidratos en la alimentación de pollos broiler en el cantón Santo Domingo. - Velásquez Trejo, Estefanía Carolina (2021)
This research details the evaluation of the use of different levels of green banana flour in the feeding of boiler chickens as a source of carbohydrates. It was carried out in the city of Santo Domingo located at 635 meters above sea level, with an average temperature of 23°C, for this research 100 Broiler chickens was used from the Cobb 500 line from one day of age until the 49th. The chickens were randomly divided into 4 groups, which underwent treatments with different levels (2, 4 and 6%) inclusion of green banana flour (Musa X Paradisiaca) in the food. Witness treatment was identified as T0 (Base diet without addition of banana flour), T1 (base diet + 2% green banana flour), T2 (base diet + 4% green banana flour) and T3 (base diet + 6% green banana flour). The bromatological characterization of green banana flour was performed to verify the composition. The study was developed over 7 weeks (49 days) in which different daily and weekly parameters were recorded such as food consumption, weight gain, deceases among others for further analysis. A completely random design (DCA) was applied with five repetitions per treatment, the weight of the experimental units at reception was homogeneous (CV: 8.67). The variance analysis was performed, with Duncan significance tests at 5%, to differentiate between treatments. The economic analysis was performed by calculating the profit-to-cost ratio (RBC). The most obvious results in the different phases were obtained by T2 treatment animals with an average weight in the first stage of 449g, at growth 1967 and ended up with an average weight of 2850g, in terms of channel performance a CV of 7.23 was evident.